Macro- and micronutrients in metabolic (dysfunction) associated fatty liver disease: association between advanced fibrosis and high dietary intake of cholesterol/saturated fatty acids - (:unkn) unknown (My University, 2021)
BACKGROUND AND AIM: There is still no approved pharmacotherapy for metabolic (dysfunction) associated fatty liver disease (MAFLD). Although dietary and lifestyle modifications for weight loss remain the mainstay for disease management, the association between macro- and micronutrients and fibrosis stage in patients with MAFLD remains unclear. This study was undertaken to address this issue. METHODS: This is a retrospective analysis of prospectively collected data from patients in whom MAFLD was diagnosed with vibration controlled transient elastography. Steatosis was defined by a controlled attenuation parameter ≥238 dB/m, whereas a liver stiffness measurement ≥11 kPa was considered to indicate advanced fibrosis. RESULTS: The study sample consisted of 106 patients with MAFLD (mean age 49 ± 10 years, 52 men and 54 women). Among the different micro- and macronutrients tested, only the dietary intake of cholesterol and saturated fatty acid (SFA) was independently associated with the presence of advanced fibrosis. CONCLUSION: Our findings suggest that cholesterol/SFA-restricted dietary regimens - as exemplified by the traditional Mediterranean diet - may reduce the risk of advanced fibrosis in patients with MAFLD.